2020
DOI: 10.1016/j.celrep.2020.108235
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Proteomic Analysis of Herpes Simplex Virus 1 Infection Reveals Cell-Surface Remodeling via pUL56-Mediated GOPC Degradation

Abstract: Summary Herpesviruses are ubiquitous in the human population and they extensively remodel the cellular environment during infection. Multiplexed quantitative proteomic analysis over the time course of herpes simplex virus 1 (HSV-1) infection was used to characterize changes in the host-cell proteome and the kinetics of viral protein production. Several host-cell proteins are targeted for rapid degradation by HSV-1, including the cellular trafficking factor Golgi-associated PDZ and coiled-coil motif-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 100 publications
(136 reference statements)
9
36
0
Order By: Relevance
“…GST pull-down experiments using reagents purified following recombinant expression in Escherichia coli (pUL21 and PP1γ) and HEK293F cells (CERT) confirmed that pUL21 binds directly to both PP1 and CERT (Fig 1C). Published quantitative viromics analysis [27] confirms that the abundance of CERT and all three PP1 catalytic subunit isoforms is unchanged in keratinocytes over the course of HSV-1 infection.…”
Section: Resultsmentioning
confidence: 84%
“…GST pull-down experiments using reagents purified following recombinant expression in Escherichia coli (pUL21 and PP1γ) and HEK293F cells (CERT) confirmed that pUL21 binds directly to both PP1 and CERT (Fig 1C). Published quantitative viromics analysis [27] confirms that the abundance of CERT and all three PP1 catalytic subunit isoforms is unchanged in keratinocytes over the course of HSV-1 infection.…”
Section: Resultsmentioning
confidence: 84%
“…S1 B ). Using multiplexed quantitative proteomic analysis over the whole time course of HSV-1 infection, it has recently been shown that the viral glycoproteins gM and gC follow similar kinetic expression profiles ( 20 ). We demonstrate first by using time-lapse imaging that indeed gM behaves in a similar way to gC, which allows for spatial and temporal correlation with our previous data sets acquired with the timestamp virus ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblotting for phosphorylated Akt substrates in HSV-1 infected cells reveals additional proteins targeted by pUL21 for PP1-mediated dephosphorylation that have yet to be identified and confirms that pUL21 has a broad specificity that overlaps with, but is not identical to, that of pUS3. In contrast to pUS3, which is expressed immediately after infection and plateaus at around 6 hours post-infection (hpi), pUL21 is a late gene and its abundance increases steadily as the infection progresses (Soh et al, 2020). One could thus hypothesise that pUL21 confers temporal regulation of pUS3-dependent protein phosphorylation, promoting dephosphorylation of specific pUS3 substrates at late times post-infection to ensure coordinated progression of virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry analysis was performed by the proteomics facility of the University of Bristol (UK) as described in (Soh et al, 2020). The raw data files were processed using MaxQuant v. 1.5.6.0 (Cox and Mann, 2008).…”
Section: Gfp Affinity Capture and Quantitative Mass Spectrometrymentioning
confidence: 99%